Contribución de la historia y de la filosofía de las ciencias al desarrollo de un modelo de enseñanza/aprendizaje como investigación - Gil Pérez, D. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
After the fiasco of the «Iearning by discover y» orientation and the serious limitations of the «reception learning» paradigm, a new consensus is emerging on the nature of mathematics and science learning as a construction of knowledge. These constructivist approaches have taken explicitly into account contemporary views in philosophy of science as an epistemological base for a conception of learning as a conceptual change. Teaching strategies oriented to produce conceptual changes have been developed with promising results, but serious difficulties have also appeared. Our contribution will try to show that those difficulties are due to a still insufficient consideration of the nature of science in the teaching strategies. Consequently, we shall propose some modifications of these strategies, taking more carefully into account the relationship between the nature of science and the nature of learning.